Cervical cancer screening coverage in the Americas region: a synthetic analysisResearch in context - Ginna Fernández-Deaza; Beatriz Serrano; Esther Roura; Juan Sebastián Castillo; María Caicedo-Martínez; Laia Bruni; Raúl Murillo (Elsevier, 2024)
Summary: Background: The Americas region has the lowest (North America) and the second highest (Latin America and Caribbean) cervical cancer (CC) mortality worldwide. The lack of reliable data on screening coverage in the region hinders proper monitoring of the World Health Organization (WHO) CC elimination initiative. Methods: For this synthetic analysis, we searched data on CC screening coverage from official sources and national health surveys, supplemented with a formal WHO country consultation. Context data were obtained from official sources (income, health expenditure, inequality-adjusted human development index -IHDI-, universal health coverage, CC incidence/mortality). Country age-specific coverages for 2019 by screening interval were computed. Missing data were imputed through a multi-step algorithm. Beta-regression and Poisson-regression models were used to analyse associations between context variables, screening coverage, and CC mortality. Findings: We included data from 37 countries in the Americas. Data on coverage of HPV testing was scarce, and for many countries only Pap-smear coverage data was available. Overall, 78%, 34%, 60%, and 67% of women aged 25-65 years have been screened ever in their lifetime, and in the previous year, 3 years, and 5 years, respectively. By sub-region, 3-year coverage ranges from 48% (South America) to 72% (North America). Twenty-four countries showed screening coverage below 70%. Income and health system type were associated with screening coverage, but coverage was not associated with CC mortality. Interpretation: In the Americas region 35.1% and 56.8% of countries report 3-year and 5-year coverage over 70%, respectively. Inequalities remain a major challenge for screening programs in the region. The elimination campaign should reinforce the transition to HPV testing and strengthen surveillance systems. Funding: Instituto de Salud Carlos III, European Regional Development Fund, Secretariat for Universities and Research of the Department of Business and Knowledge of the Government of Catalonia, and Horizon 2020.